Analysis of the backpressure effect of an Organic Rankine Cycle (ORC) evaporator on the exhaust line of a turbocharged heavy duty diesel power generator for marine applications. (15th January 2017) - Michos, Constantine N.; Lion, Simone; Vlaskos, Ioannis; Taccani, Rodolfo
Highlights: Waste heat recovery on internal combustion engines is studied. The backpressure effect of the Organic Rankine Cycle boiler has been evaluated. Three different state-of-the art turbocharging technologies have been assessed. Six different fluids for medium-high temperature recovery have been considered. A reduction up to 10% in fuel consumption can be achieved. Abstract: In marine and power generation sectors, waste heat recovery technologies are attracting growing attention in order to increase heavy duty diesel engines efficiency and decrease fuel consumption, with the purpose of respecting stringent emissions legislations. In this work, the backpressure effect of an Organic Rankine Cycle (ORC) evaporator on the exhaust line of a turbocharged, V12 heavy duty diesel engine, for typical marine and power generation applications has been investigated using the commercial software Ricardo WAVE. Three different state-of-the art turbocharging strategies are assessed in order to counterbalance the increased pumping losses of the engine due to the boiler installation: fixed turbine, Waste-Gate (WG) and Variable Geometry Turbine (VGT). At the same time, the steady-state thermodynamic performance of two different ORC configurations, simple tail-pipe evaporator and recuperated simple tail-pipe evaporator layouts, are assessed, with the scope of further increasing the engine power output, recovering unutilized exhaust gas heat. Several different working fluids, suitable for medium-high temperature waste heat recovery, are evaluated and screened, considering, as well, health and safety issues. Thermodynamic cycle parameters such as, for example, evaporation and condensing pressures, working fluid mass flow and cycle temperatures, are optimized in order to obtain the maximum improvement in Brake Specific Fuel Consumption (bsfc). From the engine side point of view, a VGT turbocharger is the most favorable solution to withstand increased backpressure, while, regarding the ORC side, between the considered fluids and layouts, acetone and a recuperated cycle show the most promising performance.